A noninvasive and highly sensitive approach for the assessment of coronary collateral circulation by 192-slice third-generation dual-source computed tomography. Issue 38 (September 2019) - Chen, Kebin; Zhang, Xiaoge; Li, Daling; Chen, Honglei; Zhang, Zhixu; Chen, Lei
Abstract : Abstract: The coronary collateral circulation (CCC) is an alternative source of blood supply when the original vessels fail to provide sufficient blood. The accurate detection of CCC is critical for the treatment of ischemic heart disease, especially when the stent surgery is not an option. The assessment of minute vessels such as coronary collateral arteries is challenging. The objective of this study was to assess the feasibility of detection and classification of CCC using the192-slice third-generation dual-source computed tomography angiography (192-slice DSCT CTA). Eight hundred patients (450 men and 350 women, mean age: 56 ± 11 years) with complete or subtotal occlusion of at least 1 major coronary artery were enrolled for our study. February 2016 and September 2018, the patient both 192-slice DSCT CTA and conventional coronary angiography (CAG) were performed in all enrolled patients. The interval between two approaches for a given patient was 6.1 ± 3.7 days (Range: 1–15). The diagnostic accuracy of 192-slice DSCT CTA was evaluated by comparing it with that of CAG. The identified CCC was graded according to the Rentrop classification. The prevalence among patients of having at least 1 CCC was 43.8%. The sensitivity for detecting CCC by 192-slice DSCT was 91.7% (95% CI: 88.3% to 94.3%), specificity was 95.5% (95% CI: 93.1% to 97.2%), positive predictive value was 94.3% (95% CI: 91.5% to 96.2%), and negative predictive value was 93.3% (95% CI: 90.9% to 95.3%). Cohen-Kappa analysis showed that the consistency of the correct classification of CCC using CAG and 192-slice DSCT was very high with the kappa coefficient (κ) of 0.94 (95% CI: 0.91–0.96, P value = .01). Additionally, the radiation dose for 192-slice DSCT was as low as 0.42 ± 0.04 mSv (range, 0.35–0.43 mSv). The 192-slice DSCT CTA is a reliable and sensitive non-invasive method for the evaluation of CCC with low radiation doses.